2007
DOI: 10.1007/s10528-007-9106-x
|View full text |Cite
|
Sign up to set email alerts
|

RAPD Analysis of DNA Polymorphism in Turkish Sheep Breeds

Abstract: The genetic diversity and phylogenetic relationships of 108 individual sheep from three Turkish sheep breeds (Kivircik, Gökçeada, and Sakiz) were studied using RAPD analysis. Polymorphisms within and between populations were assayed using 15 random primers, and 82 loci were amplified ranging from 250 to 2,500 bp. The percentage of polymorphic loci was found to be 80.49, 78.05, and 73.17%, for Kivircik, Gökçeada, and Sakiz sheep breeds, respectively. Total genetic diversity was 0.2265, and the average coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 16 publications
0
20
2
1
Order By: Relevance
“…Mahfouz et al (2008) also reported fifty-seven amplified bands using five random primers with a mean of 11.4 bands per primer. Contrary to the present study, low number of fragments was amplified as reported by Elmaci et al (2007) and Khalidi et al (2010). William et al (1990) and Meunier (1993) reported that polymorphic loci are useful for study the genetic variation between breeds.…”
Section: Resultscontrasting
confidence: 79%
“…Mahfouz et al (2008) also reported fifty-seven amplified bands using five random primers with a mean of 11.4 bands per primer. Contrary to the present study, low number of fragments was amplified as reported by Elmaci et al (2007) and Khalidi et al (2010). William et al (1990) and Meunier (1993) reported that polymorphic loci are useful for study the genetic variation between breeds.…”
Section: Resultscontrasting
confidence: 79%
“…However, it was not the same among the 10 populations that were studied, varying between 71.59 and 81.82% for the populations from Kavala and Mytilene, respectively (Table 2). Nevertheless, the proportion of polymorphic loci is not regarded as a good method to describe genetic variation, while more appropriate measures like effective number of alleles and heterozygosity are more efficient estimators (Elmaci et al, 2007;Tiira and Primmer, 2009). Especially for RAPD data, I is considerably suitable since it remains unaffected by the method's inability to distinguish heterozygous individuals but also does not require the presumption that populations are in Hardy-Weinberg equilibrium (Dawson et al, 1995).…”
Section: Genetic Diversitymentioning
confidence: 99%
“…These results indicated that the level of DNA variation was high among the animals studied, and these findings agreed with many researchers as [21] revealed that the percentage of polymorphic loci was 80.49, 78.05, and 73.17%, for Kivircik, Gökçeada, and Sakiz sheep breeds, respectively. Mahfouz [22], who analyzed Egyptian sheep breeds, reported that fifty six out of 57 total amplified fragments (98.25%) were polymorphic loci, and the rest were Monomorphic.Khalidi [23] analyzed three ovine breeds in Tunisia total of 59 loci were amplified, out of which 47 (79.66%) were polymorphic, andDevrim and Kaya [24] analyzed ninety-one animals for Turkish cattle breeds and eighteen random primers were screened. A total of 89 loci were amplified, out of these bands 78 (87.6%) were polymorphic; also some of the primers gave no bands in some samples.…”
Section: Results and Discussion:-mentioning
confidence: 99%